Synergistic anticancer effects of nanocarrier loaded with berberine and miR-122. Issue 3 (27th June 2018) - Li, Lei; Li, Xiao; Huang, Xin; Jiang, Weilai; Liu, Letian; Hou, Chunning; Yang, Yanqing; Zhang, Lei; Zhang, Xiaodan; Ye, Longwei; Yuan, Jie; Li, Guolin; et al.
Abstract : We introduced polyethyleneimine (PEI)-cholesterol (PC) as a nanocarrier incorporating berberine (BER) and miR-122 for the treatment of oral squamous cell carcinoma (OSCC). BER was stabilized by incorporating PC to form ber -PC. Ber -PC was further electrostatically complexed with miR-122 to yield mr-ber- PC for the co-delivery of BER and miR-122. mr-ber- PC treatment dramatically decreased the level of invasion and migration of OSCC cells compared with single drug treatments. The present study suggested that PC could be a multifunctional nanocarrier for the co-delivery of anticancer drug BER and miR-122 to significantly increase the anticancer therapeutic effects.